The Role of Waqf in Strengthening Primary Healthcare Services in Gombe State Rural Communities - Muhammad, Adamu Abubakar; Mikail, Usman Jibril; Ahmad, Muhammad Hamma Adama; Ardo, Adam Muhammad; Wani, Athar Shahbaz; Khatoon, Ghousia (CV Media Inti Teknologi, 2025)
Background of study: This study examines the advantages, difficulties, and prospective advancements of Waqf in bolstering primary healthcare services in Gombe State's rural regions. Waqf, an Islamic endowment for social welfare, has long provided funding for healthcare and education, but its ability to provide rural health care is still restricted.Aims and scope of paper: The study intends to evaluate the role Waqf institutions play in primary healthcare and offer solutions for enhancing their sustainability and effectiveness in rural Nigeria.Methods: Qualitative and quantitative data were combined in a mixed-methods approach. Structured interviews and questionnaires with Waqf administrators, healthcare providers, legislators, and community members were used to collect primary data. Official reports, pertinent literature, and case studies of effective Waqf-based healthcare projects were examples of secondary data. The data was interpreted using thematic analysis and descriptive statistics.Result: The results show that Waqf institutions build facilities, offer subsidized medical services, and help staff in order to give vital healthcare support. Their efficacy is hampered by issues like low public knowledge, shoddy legislative frameworks, erratic funding, inadequate asset management, and little cooperation with government organizations. Important suggestions include bolstering relationships, strengthening legal and policy frameworks, and promoting financial sustainability through investment.Conclusion: According to the study's findings, Waqf can be a long-term source of finance for rural healthcare with effective management, lowering reliance on government and outside assistance while fostering fair access to healthcare throughout Gombe State.